TRANSFORMASI REPRESENTASI SEJARAH DALAM SASTRA KONTEMPORER INDONESIA - Ratu Pangestu (Journal of Linguistics, Literature, Culture and History, 2025)
The relationship between history and literature in Indonesia is strong and complementary, with history serving as a crucial source of inspiration for literary works. Indonesian historians and writers have demonstrated the close relationship between history and literature in Indonesian culture, where literary works often take the form of "stories" that can contain both verbal and fictional elements that lend deeper meaning to historical events. This study aims to examine how history is transformed in contemporary Indonesian literature and the aesthetic, political, and cultural purposes of these historical representations. This study uses a descriptive qualitative approach, utilizing the theory of New Historicism, to examine the relationship between literary texts and their historical contexts. Indonesian literature has a rich history, spanning from the Balai Pustaka era to the New Order and Reformation eras. Initially, literature was influenced by the socio-political context and presented normatively to support official narratives. However, during the Reformation and contemporary eras, history has been treated more critically and is open to various interpretations.